Lifetime prediction in medium-cycle fatigue regime of notched specimens. (August 2016) - Negru, R.; Șerban, D.A.; Marșavina, L.; Magda, A.
Highlights: Three methods were assessed to predict lifetime of notched components. Three notched components were considered (semi-circular and two V -notches). The predicted results are compared with experimental fatigue data. Good predictions were obtained for line method on TCD, volumetric method and SED. Predictions for V -notches are accurate than those on semicircular notches. Abstract: This paper assesses three methods (Theory of Critical Distances, Volumetric method and Strain Energy Density) for the lifetime prediction of notched components in medium-cycle fatigue. The predictions are compared with experimental fatigue data, obtained by authors by testing aluminium 2024-T3 specimens with semi-circular and two types of V -notches. The presented methods, based on simple FEM analysis, could successfully substitute time-consuming experimental fatigue tests.